Retrieving the in vivo Scopoletin Fluorescence Excitation Band Allows the Non-invasive Investigation of the Plant–Pathogen Early Events in Tobacco Leaves - Agati, Giovanni; Brunetti, Cecilia; Tuccio, Lorenza; Degano, Ilaria; Tegli, Stefania (Frontiers in Microbiology, 2022)
We developed and applied a new spectroscopic fluorescence method for the in vivo detection of the early events in the interaction between tobacco (Nicotiana tabacum L.) plants and pathogenic bacteria. Leaf disks were infiltrated with a bacterial suspension in sterile physiological solution (SPS), or with SPS alone as control. The virulent Pseudomonas syringae pv. tabaci strain ATCC 11528, its non-pathogenic ΔhrpA mutant, and the avirulent P. syringae pv. tomato strain DC3000 were used. At different post-infiltration time-points, the in vivo fluorescence spectra on leaf disks were acquired by a fibre bundle-spectrofluorimeter.. The excitation spectra of leaf blue emission at 460 nm, which is mainly due to the accumulation of coumarins following bacterial infiltration, were processed by using a two-bands Gaussian fitting that enabled us to isolate the scopoletin (SCT) contribution. The pH-dependent fluorescence of SCT and scopolin (SCL), as determined by in vitro data, and their intracellular localization, as determined by confocal microscopy, suggested the use of the longer wavelength excitation band at 385 nm of 460 nm emission (F385_460) to follow the metabolic evolution of SCT during the plant-bacteria interaction. It was found to be directly correlated (R2 = 0.84) to the leaf SCT content, but not to that of SCL, determined by HPLC analysis. The technique applied to the time course monitoring of the bacteria-plant interaction clearly showed that the amount and the timing of SCT accumulation, estimated by F385_460, was correlated with the resistance to the pathogen. As expected, this host defence response was delayed after P. syringae pv. tabaci ATCC 11528 infiltration, in comparison to P. syringae pv. tomato DC3000. Furthermore, no significant increase of F385_460 (SCT) was observed when using the non-pathogenic ΔhrpA mutant of P. syringae pv. tabaci ATCC 11528, which lacks a functional Type Three Secretion System (TTSS). Our study showed the reliability of the developed fluorimetric method for a rapid and non-invasive monitoring of bacteria-induced first events related to the metabolite-based defence response in tobacco leaves. This technique could allow a fast selection of pathogen-resistant cultivars, as well as the on-site early diagnosis of tobacco plant diseases by using suitable fluorescence sensors.